In-process measurement and monitoring of a polymer laser sintering powder bed with fringe projection - Southon, Nicholas; Stavroulakis, Petros; Goodridge, Ruth; Leach, Richard (Elsevier, 2018)
We investigate the feasibility of using fringe projection to monitor the powder bed of a polyamide 12 polymer laser sintering machine. In particular, we demonstrate the ability of fringe projection to identify a number of defects arising during the printing process by recording the three-dimensional structure of the sintered powder bed after the completion of each layer. The defects identified ranged in size from hundreds of micrometres to hundreds of millimetres. The three-dimensional analysis of the powder bed data has shown the ability to quantify effects, such as curling, powder spreader blade interactions and the consolidation of a sintered layer. It has, therefore, been shown that the use of fringe projection in polymer laser sintering machines can provide deeper understanding and monitoring of the dynamic behaviour during the process. Fringe projection has shown potential to become part of a feedback and control system that interrupts the build and corrects for in-process defects where possible.